2016
DOI: 10.18632/oncotarget.13848
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in nucleotide excision repair genes and risk of primary prostate cancer in Chinese Han populations

Abstract: Genetic variants of nucleotide excision repair (NER) genes have been extensively investigated for their roles in the development of prostate cancer (PCa); however, the published results have been inconsistent. In a hospital-based case-control study of 1,004 PCa cases and 1,055 cancer-free controls, we genotyped eight potentially functional single nucleotide polymorphisms (SNPs) of NER genes (i.e., XPC, rs2228001 T>G and rs1870134 G>C; XPD, rs13181 T>G and rs238406 G>T; XPG, rs1047768 T>C, rs751402 C>T, and rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Moreover, excision repair cross-complementation group 1 (ERCC1), replication protein A (RPA), RAD23 homolog A (RAD23A), and RAD23 homolog B (RAD23B) also participate in NER 7 . SNPs in NER genes have been linked to various cancer types, including lung, bladder, skin, breast, prostate, and head and neck cancers 8, 9, 10, 11, 12, 13, 14, 15, 16. Accumulating evidence has indicated that some SNPs in DNA repair genes or their regulatory elements can induce phenotypical alterations, affecting DNA repair capacity and promoting cancer initiation and development.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, excision repair cross-complementation group 1 (ERCC1), replication protein A (RPA), RAD23 homolog A (RAD23A), and RAD23 homolog B (RAD23B) also participate in NER 7 . SNPs in NER genes have been linked to various cancer types, including lung, bladder, skin, breast, prostate, and head and neck cancers 8, 9, 10, 11, 12, 13, 14, 15, 16. Accumulating evidence has indicated that some SNPs in DNA repair genes or their regulatory elements can induce phenotypical alterations, affecting DNA repair capacity and promoting cancer initiation and development.…”
Section: Introductionmentioning
confidence: 99%
“…In these publications, sample sizes ranged from 96 to 1900 cases and from 101 to 1977 control subjects. Among the studies, 10 focused on gastric cancer [ 21 , 23 , 27 , 29 , 30 , 32 34 , 38 , 39 ], three focused on breast cancer [ 25 , 35 , 36 ], two focused on hepatocellular carcinoma [ 20 , 37 ], and one each focused on lung cancer [ 19 ], oral squamous cell carcinoma [ 22 ], salivary gland tumor [ 24 ], nasopharyngeal carcinoma [ 26 ], neuroblastoma [ 28 ], colorectal cancer [ 31 ], and prostate cancer [ 40 ]. Of the publications, 12 had quality scores higher than nine, and 10 had quality scores of no more than nine.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, most of the investigations were focused on rs17655 G>C (Asp1104His). The association between XPG gene rs751402 C>T polymorphism (located at the 5′ untranslational region) and cancer risk has been investigated in several studies [ 19 – 40 ], but the findings were contradictory and inconclusive. Therefore, we performed this meta-analysis with all eligible publications to comprehensively evaluate the association of XPG gene rs751402 C>T polymorphism with overall cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find any direct association of the rs4134822 and rs1799793 with NMSC risk after covariates adjustment. Previously, many studies have focused on the association between NER gene and some other diseases, including prostate cancer [ 19 ], gastric cancer [ 20 ] and thyroid cancer [ 21 ]. Several studies [ 11 15 ] were also performed on association between SNPs within NER gene and NMSC risks, but the limited number for these articles could not concluded a consistent result on this association, and could not clarify the mechanism between NER gene and NMSC susceptibility.…”
Section: Discussionmentioning
confidence: 99%